Comparative assessment of the efficacy of low concentration bleaching agents using quantitative light induced fluorescence in removing stains: An In vitro study - Aiswarya Balakrishnan; Nandlal Bhojraj; Raghavendra Shanbhog; K P Ashwini (Wolters Kluwer Medknow Publications, 2022)
Background: Tooth discoloration has become a common esthetic problem in recent years. Removal of stains by bleaching is well-documented. Low concentration home bleaching products are available in market in different forms and concentrations. Aim: The aim of this study is to evaluate and compare the efficacy of low concentration commercially available home bleaching products (whitening strip, gel, and mouthwash) in removing stains and whitening the tooth using clinical and digital methods. Materials and Methods: Sixty permanent enamel samples mounted in an acrylic block were artificially stained and randomly divided into four groups. Negative control, 15 % Carbamide peroxide gel group, 2% Hydrogen 16 peroxide mouthwash group and 6% Hydrogen peroxide strip group respectively. The samples were bleached with respective agents according to the manufacturer's instructions. The efficacy on 7th and 14th day was evaluated clinically (SGU change), photographically (ΔE), and using quantitative light-induced fluorescence (ΔF). The data were analyzed using paired t-test and analysis of variance. Results: Postbleaching, 6% hydrogen peroxide strips and 15% carbamide peroxide gel showed maximum improvement (ΔΔF - 15.73 and 11.89, ΔE - 19.8 and 18.9, respectively) when compared to 2% hydrogen peroxide mouthwash and negative control group (ΔΔF - 9.68 and 6.59, ΔE - 15.04 and 9.44, respectively). The difference was statistically significant (P = 0.001). Conclusion: 6% hydrogen peroxide strips and 15% carbamide peroxide gel showed maximum improvement in stain removal and tooth whitening however, the strips showed better efficacy than the gel. Strips have the added advantage of lesser contact period, less salivary dilution, and no gingival contact. Therefore, strips can be a better alternative for gels and mouthwashes.